Undergraduate dental students' perspective on the implementation of digital dentistry in the preclinical curriculum: a questionnaire survey - Maximiliane Amelie Schlenz; Karin Michel; Kerstin Wegner; Alexander Schmidt; Peter Rehmann; Bernd Wöstmann (BMC, 2020)
Abstract Background Digitalisation is an expanding field in dentistry and implementation of digital teaching methods in dental education is an essential part of modern education. Therefore, two digital training modules were implemented in the preclinical curriculum at the Justus Liebig University Giessen. The aim of this study was to assess the students' perspective on the implementation with a questionnaire survey. Methods Since the fall term 2017/18, students of the course of dental prosthodontics I attended the training module I, where they learned to use computer-aided learning (CAL) approaches for the digital analysis of tooth preparations. In training module II, students of the course of dental prosthodontics II learned how to manufacture a computer-aided design/computer-aided manufacturing restoration. After the completion of the training modules, all students starting with the fall term 2017/18 to the spring term 2019 were asked to fill in a questionnaire regarding the aspects of handling, didactic benefit, motivation, and overall assessment. Results Students rated the implementation of digital aspects in teaching as positive in terms of handling, didactic benefit, and motivation, but gave preference to the assessment of the tooth preparations by dental instructors. In addition, students assessed the feedback from the faculty regarding tips and tricks better than the digital feedback. More than 90% of the students indicated that they could imagine using an intraoral scanner for treatment of patients in the dental office in future. Conclusions The results of the present study revealed a positive perspective of students on the implementation of digital dentistry in the preclinical curriculum. However, difficulties with CAL systems were reported and most students preferred evaluation of preparation by dental instructors. Thus, CAL approaches offer an additional teaching method besides the traditional teaching of manual skills.